The use of composites coatings for inhibiting the chemical corrosion in metallic reservoirs - الساعدي, د.سامر عبد الكاظم صبيح (Journal of Petroleum Research and Studies, 2020)
The research aimed the identify on level of nanocomposite coating of a steel alloy that used in manufacture of mineral reservoirs for the storage of oil products in the oil products distribution company (Opdc.).. The metal was coated by epoxy composite reinforced by hybrid particles. The chemical composition of alloy was characterized by using spectrometer OE. The topographic and surface nature of coat material was studied by atomic force microscope (AFM) and optical microscope. Also a cognitive scale was prepared from (hardness, adhesion strength, chemical corrosion tests as well as electrochemical corrosion test. It was found the type is (St-37), it’s a low carbon steel according to (ASTM). It was found Hardness of coat increase with increase of reinforced ratio and the adhesion strength of coating (232 Psi). Chemical and electrochemical corrosion tests have shown the efficiency of coating in corrosion inhibiting and metal protection.